2010
DOI: 10.1089/sur.2009.015
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Community-Acquired USA300 Methicillin-ResistantStaphylococcus aureusPyomyositis and Septic Pulmonary Emboli in an Immunocompetent Adult

Abstract: The clinical history and management of severe disseminated pyomyositis, including diagnostic modalities, antimicrobial therapy, and surgical drainage, require an aggressive approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The sequences were translated to spa types according to Ridom and Kreisworth conventions [11]. Variable tandem nucleotide repeat (VNTR) typing was performed as described previously [12,13].…”
Section: Strain Typingmentioning
confidence: 99%
“…The sequences were translated to spa types according to Ridom and Kreisworth conventions [11]. Variable tandem nucleotide repeat (VNTR) typing was performed as described previously [12,13].…”
Section: Strain Typingmentioning
confidence: 99%
“…6 S. aureus is the most common pathogen isolated in up to 90% from blood cultures or surgical specimens. 7 Other bacteria implicated are S. pyogenes, S. pneumoniae, Neisseria spp. and Aeromonas spp., among others.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Recently, septic pulmonary emboli arising from primary deep tissue infections such as pyomyositis, cellulitis, osteomyelitis, prostatic and periproctal abscess have been described in the adult population. [8][9][10][11][12][13] A recent systematic review of 76 articles consisting of a total 168 cases by Ye et al 14 in 2014 showed that major risk factors for SPE were intravenous drug use, intravascular indwelling catheter and skin or soft tissue purulent infection. Seventeen cases died and 101 cases were cured.…”
Section: Discussionmentioning
confidence: 99%